2004
DOI: 10.1086/423715
|View full text |Cite
|
Sign up to set email alerts
|

Time Constraints Decouple Age and Size at Maturity and Physiological Traits

Abstract: Life-history theory predicts changes in age and size at maturity in response to constraints in animals with complex life cycles. A critical underlying assumption is that only these traits are optimized during ontogeny. However, it is not clear how altered life histories mechanistically translate into survival and fecundity. Here we present data from damselflies reared from egg to adult under day lengths mimicking the start or end (time constrained) of the season at high and low food level. These data show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 37 publications
(32 reference statements)
5
76
0
Order By: Relevance
“…The photoperiod did not affect the sign or magnitude of genetic correlations. Although in most other studies insects accelerated their development when time-constrained Stoks, 2003, 2004), Rolff et al (2004) found this only for time-constrained damselflies, which were additionally food-constrained. Most probably all larvae kept at high food level had already attained their minimum development time so that any further acceleration was not possible (Rolff et al, 2004).…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…The photoperiod did not affect the sign or magnitude of genetic correlations. Although in most other studies insects accelerated their development when time-constrained Stoks, 2003, 2004), Rolff et al (2004) found this only for time-constrained damselflies, which were additionally food-constrained. Most probably all larvae kept at high food level had already attained their minimum development time so that any further acceleration was not possible (Rolff et al, 2004).…”
Section: Discussionmentioning
confidence: 78%
“…Recent work suggests that part of the variation in fitness can be explained by changes in physiological traits (Zera and Harshman, 2001;Rolff et al, 2004), such as immunity (Rolff and Siva-Jothy, 2003;Schmid-Hempel, 2003). For example, changes in photoperiod alter growth trajectories and can decouple life history and physiological traits (Rolff et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations